Alignment between nationally determined contributions and the sustainable development goals for West Africa. (26th November 2018) - Antwi-Agyei, Philip; Dougill, Andrew J.; Agyekum, Thomas P.; Stringer, Lindsay C.
ABSTRACT: The UN Sustainable Development Goals (SDGs) and the 2015 Paris Agreement are two of the most important policy frameworks of the twenty-first century. However, the alignment of national commitments linked to them has not yet been analysed for West African states. Such analyses are vital to avoid perverse outcomes if states assess targets and develop SDG implementation plans, and Nationally Determined Contributions (NDC) under the Paris Agreement, without integrated planning and cross-sectoral alignment. This article provides a situation analysis guided by the following questions: (a) Which priority sectors are mentioned in relation to adaptation and mitigation in West African NDCs? (b) Are the NDCs of West African states well aligned with the SDGs? (c) What are the co-benefits of NDCs in contributing towards the SDGs? and (d) How are West African states planning to finance actions in their NDCs? The study uses iterative content analysis to explore key themes for adaptation and mitigation within NDCs of 11 West African states and their alignment to selected SDGs. A national multi-stakeholder workshop was held in Ghana to examine the co-benefits of the NDCs in contributing towards the SDGs and their implementation challenges. Results show that agriculture and energy are priority sectors where NDCs have pledged significant commitments. The analysis displays good alignment between mitigation and adaptation actions proposed in NDCs and the SDGs. These represent opportunities that can be harnessed through integration into national sectoral policies. However, cross-sectoral discussions in Ghana identify significant challenges relating to institutional capacity, a lack of coordination among institutions and agencies, and insufficient resources in moving towards integrated implementation of national planning priorities to address successfully both NDC priorities and the SDGs. Key policy insights Positive alignments between West African NDCs and SDGs present opportunities for mutual benefits that can advance national development via a more climate resilient pathway. NDCs of West African states can provide mutual benefits across the water–energy–food nexus, such as through climate-smart agriculture and low carbon energy technologies. Ghanaian multi-sectoral insights show the need to empower national coordinating bodies to overcome misalignments across different sectors.